Multi-carbonyl naphthalene diimide polymer as a high-performance cathode for stable lithium-ion storage - Hewei Luo; Feigen Xiong; Haonan Bai; Chen Wang; Yang Wang; Kang Zhao; Ji Yan; Yong Zhang; Junwei Ding; Shiwen Wang; Linsen Zhang; Juchen Guo; et al. (Nano Research Energy)
Organic materials are emerging candidates for lithium-ion batteries. Unfortunately, limited electrical conductivity and high solubility in organic electrolytes usually cause low capacity and short cycle life, which hinder the utilization of organic materials. Herein, a novel multi-carbonyl naphthalene diimide non-conjugated polymer (NDI-BU) has been readily synthesized through one-step reaction. The designed polymer structure of NDI-BU shows a long and flat discharge platform. The abundant carbonyls provide multiple reaction sites for lithium ions, and resulting in a high specific capacity of 308 mAh·g–1 at 0.2C. An incredibly long cycle life of 20,000 cycles at 5C with 82% capacity retention is achieved. This work may inspire the effective design strategy for high energy density organic cathode materials.